The Concept of Purity in Ancient Anatolian Religions: Water’s Sanctity in Purification - Nuriye Külahlı (Anadolu Araştırmaları)
Purification, considered essential in ancient Anatolia, was the crown of religious rituals. Providing the most comprehensive archive of ancient Anatolia, The Hittite texts have many terms related to purity. These terms indicate that physical and spiritual purification was the most important condition of the rituals organized for Hittite, Hurrian, and Luwian deities within Hittite syncretism. In Hittite texts, the term “water” most frequently used for purification and mentions that the person must be clean by performing purification rituals. The main purpose of these rituals is spiritual purification. Existing findings in Anatolia indicate that purification continued in the religious rituals of the Phrygians, Lydians, Lycians, and Urartians. The aim of this study is to examine the sanctity of water in rituals in light of Hittite texts and modern sources through the cross-cultural development of the concept of physical and spiritual purity in ancient Anatolian religions and to identify the factors that led to this development. In this context, the sanctity of water in the religions of the Anatolian civilizations from the historical ages to the end of the Iron Age will be examined and the continuity of the issue will be discussed.